Germline mutations in PPFIBP2 are associated with lethal prostate cancer. Issue 16 (24th July 2018) - Wu, Yishuo; Yu, Hongjie; Zheng, Siqun Lilly; Feng, Bingjian; Kapron, Ashley L.; Na, Rong; Boyle, Julie L.; Shah, Sameep; Shi, Zhuqing; Ewing, Charles M.; Wiley, Kathleen E.; Luo, Jun; et al.
Abstract : Background: Few genes have germline mutations which predispose men to more aggressive prostate cancer (PCa). This study evaluated the contribution of germline loss of function (LOF) variants in PPFIBP2 to risk of lethal PCa. Methods: A case‐case study of 1414 PCa patients with lethal PCa and low‐risk localized PCa was performed. Germline DNA samples from these patients were sequenced for PPFIBP2 . Mutation carrier rates and association with lethal PCa were analyzed using the Fisher exact test, logistic regression, and Kaplan‐Meier survival analysis. Results: In the entire study population, eight patients, all of European ancestry, were identified as carrying PPFIBP2 pathogenic or likely pathogenic mutations. Seven (1.52%) of 462 lethal PCa patients were carriers compared with only one (0.12%) carrier in 810 low‐risk PCa patients, P = 0.0029. The estimated Odds Ratio (OR) of carrying PPFIBP2 mutation for lethal PCa was 13.8 in European American population. The PPFIBP2 loss‐of‐function mutation carrier rate in lethal PCa cases was also higher than in 33 370 non‐Finnish European individuals from the Exome Aggregation Consortium (ExAC) (carrier rate of 0.17%, P = 1.92 × 10 −5 ) and in 498 men with localized PCa from The Cancer Genome Atlas cohort (TCGA) cohort (carrier rate of 0%, P = 0.0058). Survival analysis in European American lethal cases revealed PPFIBP2 mutation status as an independent predictor of shorter survival after adjusting for age at diagnosis, PSA at diagnosis, and genetic background (hazard ratio = 2.62, P = 0.034). Conclusions: While larger studies are needed, germline mutations in a novel gene, PPFIBP2, differentiated risk for lethal PCa from low‐risk cases and were associated with shorter survival times after diagnosis.